Ocean Bottom and deep-towed controlled source electric field data during cruise MSM63 on May 3rd to 5th 2017 across Scanner Pockmark, UK North Sea - Romina A S Gehrmann; Tim A Minshull; Naima K Yilo; Christian Berndt (PANGAEA, 2023)
Ocean Bottom and deep-towed controlled source electric field data during cruise MSM63 with electromagnetic source DASI (University of Southampton), electric field receivers Vulcan (UoS, Scripps), and Ocean bottom receivers (Ocean Bottom Instrument Facility, UK).